Targeted Poverty Alleviation Lies in Precisely Identifying the Poverty–Stricken Population: An Analysis of the Targeting Effect of the Rural Subsistence Allowance Policy - Zhu Mengbing (Contemporary Social Sciences, 2018)
Poverty–stricken populations must be identified precisely in the fight against poverty to implement the strategy of building a moderately prosperous society in all respects by 2020. The analysis based on the household survey in 2013 shows that the targeting accuracy is not high based on the standard of income and the accuracy is higher based on the standard of multidimensional poverty index. But the latter still has a low coverage rate. To gradually achieve integration of the rural poverty line and the rural subsistence allowance line, standards applied to identifying households entitled to subsistence allowances should be changed from the standard of income to multidimensional poverty indexes. A unified standard of subsistence allowances and a unified method for identifying related households should be developed. At the same time, coverage and funding of subsistence allowances should be extended and increased to better meet people’s basic needs.